German automatic weapons of World War II - Bruce, Robert (Live firing classic military weapons in colour photographs, 1996)
Exceptional color photographs and an authoritative text reveal the individual charateristics of weapons used by German soldiers during WWII. Weapons are shown being handled by firers wearing authentic period uniforms and field equipment placing the weapon in its correct historical context. Weapons profiled include: Mauser Schnellfeuer machine pistol; MP40 sub-machine gun; MG34 machine gun; MG42 machine gun; FG42-I and -II paratroop assault weapons and the StG44 assault rifle.